Ultraflexible organic amplifier with biocompatible gel electrodes - Sekitani, Tsuyoshi; Yokota, Tomoyuki; Kuribara, Kazunori; Kaltenbrunner, Martin; Fukushima, Takanori; Inoue, Yusuke; Sekino, Masaki; Isoyama, Takashi; Abe, Yusuke; Onodera, Hiroshi; Someya, Takao (Nature communications, 2016)
In vivo electronic monitoring systems are promising technology to obtain biosignals with high spatiotemporal resolution and sensitivity. Here we demonstrate the fabrication of a biocompatible highly conductive gel composite comprising multi-walled carbon nanotube-dispersed sheet with an aqueous hydrogel. This gel composite exhibits admittance of 100 mS cm −2 and maintains high admittance even in a low-frequency range. On implantation into a living hypodermal tissue for 4 weeks, it showed a small foreign-body reaction compared with widely used metal electrodes. Capitalizing on the multi-functional gel composite, we fabricated an ultrathin and mechanically flexible organic active matrix amplifier on a 1.2-μm-thick polyethylene-naphthalate film to amplify (amplification factor: ∼200) weak biosignals. The composite was integrated to the amplifier to realize a direct lead epicardial electrocardiography that is easily spread over an uneven heart tissue. Flexible electronics promise the opportunity to monitor biological activity via implanted devices. Here, the authors develop a biocompatible conductive carbon nanotube/gel composite and couple it with an ultrathin flexible amplifier, enabling in vivo measurement of epicardial electrocardiogram signals.